THE PERSPECTIVES OF SUSTAINABLE DEVELOPMENT OF SERBIAS AGRICULTURE IN GLOBALIZED ENVIRONMENT - Aničić, Dušan; Nestorović, Olgica; Simić, Nataša; Miletić, Slavomir (Economics of Agriculture, 2019)
This paper has a goal to point out causes and consequences of wrong agricultural policy in transitional period which caused that agriculture of Serbia suffers a huge damage which manifested itself through falling apart of big agricultural combinats, enterprises from food industry, agricultural cooperatives and small family farms. Big changes at the end of XX and at the beginning of XXI century reflect of agriculture, too, and demand a new conceptual approach to new situation. Authors of paper point out necessity of revitalization of cooperative system and other was of joining and connecting of agricultural producers, as well as need of bigger support to small family farms, by model in developed EU countries. On that way, agriculture of Serbia would successfully respond to complex requirements of globalized environment and turn its comparative advantages into competitive ones.